The long‐standing history of Corynebacterium parvum, immunity, and viruses. Issue 11 (29th June 2020) - Palmieri, Beniamino; Vadalà, Maria; Roncati, Luca; Garelli, Andrea; Scandone, Francesco; Bondi, Moreno; Cermelli, Claudio
Abstract: We report a review of all the experimental and clinical studies performed in the last 60 years on the antiviral activity of inactivated Corynebacterium parvum (Cutibacterium acnes) . This bacterium has been originally investigated and used for its oncolytic properties linked to immunomodulating activity, but the interest to successfully prevent and treat bacterial, fungal, and viral infections and lethality, uprising the innate immunity barriers produced many experimental models and very few clinical studies. The dramatic defenseless situation due to impending CoViD‐19 pandemic claims to exhume and highlight this aspecific strategy in preventive and therapeutic settings; as a matter of fact, no new or mutated virus can potentially escape to this strong innate immune surveillance strengthened by adequate C. parvum protocols.